1994
DOI: 10.1111/j.1532-5415.1994.tb01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Falls after Hospital Discharge

Abstract: There is a high incidence of falls after hospital discharge, particularly among patients who are functionally dependent. Further study is needed to determine to what extent acute illness and hospitalization may influence falls risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 44 publications
(74 reference statements)
1
102
1
Order By: Relevance
“…Research highlights a number of common discharge-related risks associated, for example, with the management of medicines, the provision of appropriate health and social care, incomplete tests and scans, the fitting and use of home adaptation, and the risks of falls, infections or sores. [17][18][19][20][21][22][23][24][25][26][27][28] The underlying sources of these risks can range from factors related to the patient's condition or comorbidities, to the assessment of patient need, the availability of specialist resources in the community, and wider organisational and cultural factors. For example, research shows that the patient's condition, such as hip fracture, and other comorbidities, especially cognitive function and fragility, can represent a cluster of risks, particularly for older patients, that can complicate the discharge process.…”
Section: Hospital Discharge and Patient Safety: Reviews Of The Literamentioning
confidence: 99%
“…Research highlights a number of common discharge-related risks associated, for example, with the management of medicines, the provision of appropriate health and social care, incomplete tests and scans, the fitting and use of home adaptation, and the risks of falls, infections or sores. [17][18][19][20][21][22][23][24][25][26][27][28] The underlying sources of these risks can range from factors related to the patient's condition or comorbidities, to the assessment of patient need, the availability of specialist resources in the community, and wider organisational and cultural factors. For example, research shows that the patient's condition, such as hip fracture, and other comorbidities, especially cognitive function and fragility, can represent a cluster of risks, particularly for older patients, that can complicate the discharge process.…”
Section: Hospital Discharge and Patient Safety: Reviews Of The Literamentioning
confidence: 99%
“…A growing body of international research shows that patients often experience unsafe care before, during and after care transition, often because of the difficulties of coordinating multiple health and social care agencies. [10][11][12][13][14][15] Elaborating this view, this study suggests discharge relies upon a complex network of specialists working within the acute hospital setting, community health and social care, primary care and voluntary sectors. Analysis of the threats to safe discharge therefore requires attention to the interdependencies and interactions between these heterogeneous groups.…”
Section: Main Findingsmentioning
confidence: 99%
“…Common threats to safety are associated with medicines management, the provision of ongoing care, incomplete testing, the use of home adaptation and risks of falls, infections or sores. [11][12][13][14] Analysis of these events consistently identifies communication and coordination across occupational and organizational boundaries as influencing the quality and safety of discharge, especially the accuracy, completeness and timing of interdependent activities. [15][16][17][18] Elaborating these interdependencies, Glasby 19 describes the influence of occupational factors, related to differences in professional knowledge, cultures and practices; organizational factors related to divergent working patterns, capabilities and resources; and compatibility and coordinating factors related to how occupational and organizational differences are aligned.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that patients who use ambulation aids prior to hospitalization are at increased risk for decline in walking with hospitalization, and for falls after hospital discharge (13,14). However, the association of assistive device use with loss of ADL independence has not been evaluated.…”
mentioning
confidence: 99%